(untitled) (E Global Congress, 2024)
This article delves into the philosophical contributions of Abu Nasr Muhammad ibn Uzluq Tarkhan, better known as Al-Farabi, a renowned Eastern philosopher, polymath, and key figure in the development of medieval science. Known as the "Second Teacher," Al-Farabi made profound contributions to various philosophical and humanistic traditions, especially regarding human nature and the ideal human condition. His views on human existence, intellect, willpower, and self-organization are explored, with a focus on his nonlinear approach to understanding human nature. The article also connects Al-Farabi’s teachings to modern concepts such as synergetic methodology, which aligns with his vision of humans as self-organizing systems. It reflects on the need for innovative, self-correcting methodologies to address the complexities of human existence and society. Furthermore, the article highlights the relevance of Al-Farabi’s ideas in the context of the New Uzbekistan Development Strategy, which emphasizes human dignity, education, and well-being. The article also examines the philosophical legacy of Al-Farabi in both Eastern and Western scholarship, noting that his ideas on human nature and society have been underexplored in the framework of synergetic methodology. By revisiting his teachings, particularly those on the "virtuous city" and self-organizing systems, the article aims to integrate his insights with contemporary approaches to understanding human development.